LEGAL PLURALISM AS THE FOUNDATION OF THE STRUGGLE FOR TRADITIONAL TERRITORIES (Social and Environmental Law Journal, 2023)
This research aims to analyze the collective identities of traditional peoples and their legal subjectivities, especially with regard to territorial rights, from the perspective of the multi-territoriality of the New Latin American Constitutionalism. Even so, it tries to interpret the legal pluralism, recognized by the Federal Constitution of 1988, and highlights the violation of the rights of traditional peoples for not being able to participate in decisions about the development models they seek for themselves, being excluded from the decision . -power to make decisions about companies that may affect them. The theoretical framework corresponds to Alfredo Wagner's teachings on the concept of traditionally occupied lands; Antônio Carlos Wolkmer and the construction of a participatory community legal pluralism; and Boaventura de Sousa Santos and the epistemologies of the South. The methodology used will be descriptive-qualitative-propositional and the work will be developed from a theoretical-methodological perspective of critical hermeneutics, based on bibliographic review, with research of primary sources, based on legal, political, historical or philosophical aspects. In summary, it points out that, despite the recognition of the legal subjectivities of traditional peoples by the Federal Constitution of 1988, their rights continue to be constantly violated, and the norms are not capable of protecting such peoples from the hegemonic forces influenced by capitalism . who do not see the essentiality of traditional territories, in addition to their economic value.
Keywords: Consultation and participation; New Latin American Constitutionalism; Traditional people; Traditionally occupied territories.